Movement disorders in hereditary spastic paraplegias - Pedroso, Jose Luiz; Vale, Thiago Cardoso; Freitas, Julian Letícia de; Araújo, Filipe Miranda Milagres; Meira, Alex Tiburtino; Neto, Pedro Braga; França, Marcondes C., Junior; Tumas, Vitor; Teive, Hélio A. G.; Barsottini, Orlando G. P. (Arquivos de Neuro-Psiquiatria, 2023)
Background Hereditary or familial spastic paraplegias (SPG) comprise a group of genetically and phenotypically heterogeneous diseases characterized by progressive degeneration of the corticospinal tracts. The complicated forms evolve with other various neurological signs and symptoms, including movement disorders and ataxia.Objective To summarize the clinical descriptions of SPG that manifest with movement disorders or ataxias to assist the clinician in the task of diagnosing these diseases.Methods We conducted a narrative review of the literature, including case reports, case series, review articles and observational studies published in English until December 2022.Results Juvenile or early-onset parkinsonism with variable levodopa-responsiveness have been reported, mainly in SPG7 and SPG11. Dystonia can be observed in patients with SPG7, SPG11, SPG22, SPG26, SPG35, SPG48, SPG49, SPG58, SPG64 and SPG76. Tremor is not a frequent finding in patients with SPG, but it is described in different types of SPG, including SPG7, SPG9, SPG11, SPG15, and SPG76. Myoclonus is rarely described in SPG, affecting patients with SPG4, SPG7, SPG35, SPG48, and SPOAN (spastic paraplegia, optic atrophy, and neuropathy). SPG4, SPG6, SPG10, SPG27, SPG30 and SPG31 may rarely present with ataxia with cerebellar atrophy. And autosomal recessive SPG such as SPG7 and SPG11 can also present with ataxia.Conclusion Patients with SPG may present with different forms of movement disorders such as parkinsonism, dystonia, tremor, myoclonus and ataxia. The specific movement disorder in the clinical manifestation of a patient with SPG may be a clinical clue for the diagnosis.
Keywords: Spastic Paraplegia, Hereditary; Movement Disorders; Dystonia; Parkinsonian Disorders; Tremor